Input–Output Functions in Human Heads Obtained With Cochlear Implant and Transcranial Electric Stimulation. Issue 8 (11th November 2019) - Tran, Phillip; Richardson, Matthew L.; Zeng, Fan‐Gang
Abstract : Objectives: Electric stimulation is used to treat a number of neurologic disorders such as epilepsy and depression. However, delivering the required current to far‐field neural targets is often ineffective because of current spread through low‐impedance pathways. Here, the specific aims are to develop an empirical measure for current passing through the human head and to optimize stimulation strategies for targeting deeper structures, including the auditory nerve, by utilizing the cochlear implant (CI). Materials and Methods: Outward input/output (I/O) functions were obtained by CI stimulation and recording scalp potentials in five CI subjects. Conversely, inward I/O functions were obtained by noninvasive transcranial electric stimulation (tES) and recording intracochlear potentials using the onboard recording capability of the CI. Results: I/O measures indicate substantial current spread, with a maximum of 2.2% gain recorded at the inner ear target during tES (mastoid‐to‐mastoid electrode configuration). Similarly, CI stimulation produced a maximum of 1.1% gain at the scalp electrode nearest the CI return electrode. Gain varied with electrode montage according to a point source model that accounted for distances between the stimulating and recording electrodes. Within the same electrode montages, current gain patterns varied across subjects suggesting the importance of tissue properties, geometry, and electrode positioning. Conclusion: These results provide a novel objective measure of electric stimulation in the human head, which can help to optimize stimulation parameters that improve neural excitation of deep structures by reducing the influence of current spread. Conflict of Interest: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.